Non-aqueous electrolyte secondary battery
Patent Information
- Application Number
- CN202180083654.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-25
- Filing Date
- 2021-12-06
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2041-12-06
AI Technical Summary
[0013] According to one aspect of this disclosure, in a non-aqueous electrolyte secondary battery using a lithium transition metal composite oxide with a high Ni content as the positive electrode active material, capacity reduction during charge and discharge can be suppressed. The non-aqueous electrolyte secondary battery of this disclosure exhibits excellent charge-discharge cycle characteristics.
Smart Images

Figure CN116601796B_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to non-aqueous electrolyte secondary batteries, and more particularly to non-aqueous electrolyte secondary batteries comprising a lithium transition metal composite oxide containing Ni as the positive electrode active material. Background Technology
[0002] In recent years, lithium transition metal composite oxides with high Ni content have attracted much attention as high-energy-density cathode active materials. For example, Patent Document 1 discloses a cathode active material composed of the general formula Li x Ni 1-y-z-v-w Co y Al z M 1 v M 2 w The lithium transition metal complex oxide shown in O2 is formed, where element M is in the formula. 1 The element M is selected from at least one of Mn, Ti, Y, Nb, Mo, and W. 2 At least Mg and Ca. In addition, Patent Document 2 discloses a composite oxide, which is a lithium transition metal composite oxide containing Ni, Mn and Co, wherein at least one of Mo, W, Nb, Ta and Re is contained.
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent Application Publication No. 2006-310181
[0006] Patent Document 2: Japanese Patent Application Publication No. 2009-289726 Summary of the Invention
[0007] The problem the invention aims to solve
[0008] However, in lithium transition metal composite oxides, if the Ni content is above 80 mol%, the composite oxide structure becomes unstable, and side reactions with the electrolyte easily occur on the surface of the composite oxide particles. Therefore, a large amount of electrolyte decomposition products are generated, forming a film of decomposition products on the negative electrode surface, which is considered to reduce the charge-discharge cycle characteristics of the battery. It should be noted that the technologies disclosed in Patent Documents 1 and 2 still have room for improvement regarding cycle characteristics.
[0009] The purpose of this disclosure is to suppress capacity reduction during charge and discharge in non-aqueous electrolyte secondary batteries that use lithium transition metal composite oxides with high Ni content as the positive electrode active material.
[0010] Solution for solving the problem
[0011] The non-aqueous electrolyte secondary battery of this disclosure is characterized by having a positive electrode, a negative electrode, and a non-aqueous electrolyte. The positive electrode comprises a lithium transition metal composite oxide having a layered structure and containing at least Ni and Mo. In the lithium transition metal composite oxide, the content of Ni is 80 mol% to 95 mol% relative to the total moles of metal elements other than Li, and the content of Mo is less than 3 mol% relative to the total moles of metal elements other than Li. The negative electrode comprises a negative electrode composite material layer containing a negative electrode active material and a Mo-containing coating formed on the surface of the negative electrode composite material layer. The content of Mo in the negative electrode is 0.5 ppm to 120 ppm relative to the total mass of the lithium transition metal composite oxide in the positive electrode.
[0012] The effects of the invention
[0013] According to one aspect of this disclosure, in a non-aqueous electrolyte secondary battery using a lithium transition metal composite oxide with a high Ni content as the positive electrode active material, capacity reduction during charge and discharge can be suppressed. The non-aqueous electrolyte secondary battery of this disclosure exhibits excellent charge-discharge cycle characteristics. Attached Figure Description
[0014] Figure 1 This is a cross-sectional view of a non-aqueous electrolyte secondary battery as an example of an implementation. Detailed Implementation
[0015] As mentioned above, lithium transition metal composite oxide particles with high Ni content exhibit high activity and unstable surface structures. Therefore, it is believed that degradation of the layered structure originating from the particle surface is easily achieved due to reactions with the electrolyte, leading to a decrease in the charge-discharge cycle characteristics of the battery. The inventors have discovered that by using lithium transition metal composite oxides containing a predetermined amount of Mo, the formation and erosion of the structural degradation layer on the surface of the lithium transition metal composite oxide caused by reactions with the electrolyte are suppressed in the positive electrode, and a high-quality coating containing Mo originating from the positive electrode is formed on the negative electrode surface, thereby improving the charge-discharge cycle characteristics.
[0016] It should be noted that when using existing lithium transition metal composite oxides, the decomposition products of the electrolyte easily form a coating containing a large amount of Li on the surface of the negative electrode, which is presumably one of the factors that reduces charge-discharge cycle characteristics. In the non-aqueous electrolyte secondary battery of this disclosure, the formation of this coating is suppressed; instead, a high-quality coating containing Mo is formed on the surface of the negative electrode, resulting in a significant improvement in charge-discharge cycle characteristics.
[0017] In this specification, “value (A) to value (B)” refers to values above (A) and below (B).
[0018] The following describes in detail an example of an embodiment of the positive electrode active material for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery using the positive electrode active material disclosed herein. Hereinafter, an example is a cylindrical battery obtained by housing a wound electrode body 14 in a bottomed cylindrical outer casing 16. However, the outer casing is not limited to a cylindrical outer casing; for example, it can be a square outer casing, or an outer casing made of a laminate containing a metal layer and a resin layer. Furthermore, the electrode body can also be a stacked electrode body in which multiple positive electrodes and multiple negative electrodes are alternately stacked with separators.
[0019] Figure 1 This is a cross-sectional view of a non-aqueous electrolyte secondary battery 10, as an example of an embodiment. Figure 1 In the example, the non-aqueous electrolyte secondary battery 10 includes: a wound electrode body 14, a non-aqueous electrolyte, and a housing 16 for housing the electrode body 14 and the electrolyte. The electrode body 14 has a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 in between. The housing 16 is a bottomed cylindrical metal container with an opening on one axial side, and the opening of the housing 16 is blocked by a sealing body 17. Hereinafter, for ease of explanation, the side of the battery with the sealing body 17 is referred to as the top, and the bottom side of the housing 16 is referred to as the bottom.
[0020] Non-aqueous electrolytes comprise a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. Examples of non-aqueous solvents include esters, ethers, nitriles, amides, and mixtures of two or more of these solvents. The non-aqueous solvent may also contain halogen substitutes obtained by replacing at least a portion of the hydrogen atoms in these solvents with halogen atoms such as fluorine. Examples of electrolyte salts used are lithium salts such as LiPF6. It should be noted that the electrolyte is not limited to a liquid electrolyte and may also be a solid electrolyte using a gel polymer or the like.
[0021] The positive electrode 11, negative electrode 12, and spacer 13 constituting the electrode body 14 are all long, strip-shaped bodies, which are alternately stacked radially along the electrode body 14 by being wound in a vortex shape. The negative electrode 12 is formed to be one size larger than the positive electrode 11 to prevent lithium deposition. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in both the length and width directions (short side direction). Two spacers 13 are formed to be at least one size larger than the positive electrode 11, for example, in a manner that clamps the positive electrode 11. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.
[0022] Insulating plates 18 and 19 are respectively arranged above and below the electrode body 14. Figure 1In the example shown, the positive lead 20 extends towards the sealing body 17 through the through hole in the insulating plate 18, and the negative lead 21 extends towards the bottom of the outer casing 16 through the outer side of the insulating plate 19. The positive lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate, i.e., the cover 27, of the sealing body 17, which is electrically connected to the internal terminal plate 23, becomes the positive terminal. The negative lead 21 is connected to the inner bottom surface of the outer casing 16 by welding or the like, and the outer casing 16 becomes the negative terminal.
[0023] A gasket 28 is provided between the outer casing 16 and the sealing body 17 to ensure the airtightness of the battery interior. A groove 22 is formed on the outer casing 16, a portion of which protrudes inward to support the sealing body 17. The groove 22 is preferably formed in a ring shape along the circumference of the outer casing 16, and its upper surface supports the sealing body 17. The sealing body 17 is fixed to the upper part of the outer casing 16 by the groove 22 and the open end of the outer casing 16 that is pressed against the sealing body 17.
[0024] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cover 27 are stacked sequentially from the electrode body 14 side. Each component constituting the sealing body 17 has, for example, a circular or annular shape, and all components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and the insulating member 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat dissipation, the lower valve body 24 deforms and breaks in a manner that pushes the upper valve body 26 toward the cover 27 side, thereby blocking the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and gas is discharged from the opening of the cover 27.
[0025] The following describes in detail the positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14, especially the positive electrode active material constituting the positive electrode 11.
[0026] [positive electrode]
[0027] The positive electrode 11 has a positive electrode core and a positive electrode composite material layer disposed on the surface of the positive electrode core. The positive electrode core may use a foil of a metal stable within the potential range of the positive electrode 11, such as aluminum, or a thin film of the same metal disposed on its surface. The positive electrode composite material layer comprises a positive electrode active material, a binder material, and a conductive material, and is preferably disposed on both sides of the positive electrode core except for the portion connecting the positive electrode lead 20. The positive electrode 11 can be manufactured, for example, by coating the surface of the positive electrode core with a positive electrode composite material slurry comprising a positive electrode active material, a binder material, and a conductive material, drying the coating, and then compressing it to form a positive electrode composite material layer on both sides of the positive electrode core.
[0028] Examples of conductive materials included in the cathode composite layer include carbon black, acetylene black, Ketjen black, carbon nanotubes (CNTs), graphene, and graphite. Examples of binders included in the cathode composite layer include fluoropolymers such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide, acrylic resins, and polyolefins. These resins can also be combined with cellulose derivatives such as carboxymethyl cellulose (CMC) or its salts, and polyethylene oxide (PEO).
[0029] The positive electrode 11 comprises a lithium transition metal composite oxide having a layered structure and containing at least Ni and Mo. Hereinafter, for ease of explanation, this lithium transition metal composite oxide will be referred to as "composite oxide (Z)". The composite oxide (Z) functions as the positive electrode active material. The positive electrode active material may consist substantially only of the composite oxide (Z), with the composite oxide (Z) as the main component. It should be noted that, without prejudice to the purpose of this disclosure, the positive electrode active material may also contain composite oxides other than composite oxide (Z), or other compounds. Examples of layered structures of the composite oxide (Z) include, for example, layered structures belonging to space group R-3m and layered structures belonging to space group C2 / m. Among these, a layered structure belonging to space group R-3m is preferred for high capacity and crystal structure stability.
[0030] Composite oxides (Z) are, for example, secondary particles formed by the aggregation of multiple primary particles. The particle size of the primary particles is typically 0.05 μm to 1 μm. The median particle size (D50) of the composite oxide (Z) on a volume basis is, for example, 3 μm to 30 μm, preferably 5 μm to 25 μm. D50 refers to the particle size at which the cumulative frequency in the volume-based particle size distribution reaches 50% from the smallest particle size; it is also known as the median diameter. The particle size distribution of composite oxides (Z) can be determined using a laser diffraction-type particle size distribution measuring device (e.g., MicrotracBEL Corp., MT3000II) with water as the dispersion medium.
[0031] The composite oxide (Z) contains Ni at a concentration of 80 mol% to 95 mol% relative to the total molar amount of metal elements other than Li. By maintaining a Ni content of 80 mol% or higher, a high energy density battery is obtained. However, if the Ni content exceeds 95 mol%, the content of Mo and other metal elements becomes excessively low, compromising the stability of the layered structure of the composite oxide (Z) and failing to suppress the formation and erosion of a structural degradation layer on the surface of the composite oxide (Z). The Ni content can be 85 mol% or higher, or 90 mol% or higher. It should be noted that if the Ni content is 80 mol% or higher, the structure of the composite oxide becomes unstable, making it prone to side reactions with the electrolyte on the particle surface.
[0032] The content of Mo in the composite oxide (Z) is less than 3 mol% relative to the total moles of metal elements other than Li, preferably less than 2 mol%, and more preferably less than 1 mol%. If the content of Mo is 3 mol% or more, the layered structure of the composite oxide (Z) becomes unstable, and the charge-discharge cycle characteristics decrease. There is no particular limitation on the lower limit of the content of Mo in the composite oxide (Z), for example, it is 0.05 mol%. Furthermore, the content of Mo is preferably 0.1 mol% or more, more preferably 0.5 mol% or more, and particularly preferably 1 mol% or more. In this case, the improvement in charge-discharge cycle characteristics is more significant.
[0033] The Mo contained in the composite oxide (Z) inhibits the formation and erosion of the structural degradation layer on the surface of the composite oxide (Z) caused by reactions with the electrolyte in the positive electrode. It is believed that the high-valence Mo retains the oxygen contained in the layered structure of the composite oxide (Z) during charging and discharging, suppressing oxygen release. Furthermore, the Mo contained in the composite oxide (Z) serves as the Mo source for the coating formed on the negative electrode surface, and some of it dissolves and deposits on the negative electrode surface during charging and discharging, becoming part of the negative electrode coating. In the composite oxide (Z), Mo can exist in solid solution within the layered structure, or on the surface of primary or secondary particles. When Mo exists on the surface of primary or secondary particles of the composite oxide (Z), it can combine with other elements such as Li to form compounds. The amount of Mo dissolved can be determined using inductively coupled plasma atomic emission spectrometry (ICP-AES), electron probe microanalysis (EPMA), or energy-dispersive X-ray diffraction (EDX).
[0034] The composite oxide (Z) may contain metallic elements other than Li, Ni, and Mo. Examples of such metallic elements include Mn, Co, Al, Zr, B, Mg, Fe, Cu, Zn, Sn, Na, K, Ca, Sr, Ba, Nb, W, Mo, Si, and the like. Among them, the composite oxide (Z) preferably contains at least either Al or Mn. It is considered that neither Al nor Mn undergoes a change in oxidation number during charging and discharging, and thus the layered structure of the transition metal layer is stabilized. The content ratio of Al is preferably 1 to 10 mol% relative to the total number of moles of metallic elements other than Li, and the content ratio of Mn is preferably 3 to 20 mol% relative to the total number of moles of metallic elements other than Li.
[0035] The composite oxide (Z) may further contain at least either W or Zr. The existing state of W or Zr in the composite oxide (Z) is not particularly limited. For example, W or Zr may be present on the surfaces of primary particles and the surfaces of secondary particles of the composite oxide (Z), or may be dissolved as a solid solution in the composite oxide (Z).
[0036] An example of a suitable composite oxide (Z) is represented by the general formula Li a Ni b Mo c M d O 2-e (in the formula, 0.8≤a≤1.2, 0.80≤b≤0.95, 0<c<0.03, 0.02<d<0.20, 0≤e≤0.05, and b+c+d=1). Preferably 0.83≤b≤0.95 and 0.001≤c≤0.02, more preferably 0.85≤b≤0.94 and 0.001≤c≤0.01.
[0037] The content ratios of the elements constituting the composite oxide (Z) can be measured using an inductively coupled plasma optical emission spectrometer (ICP-AES), an electron probe microanalyzer (EPMA), an energy-dispersive X-ray analyzer (EDX), or the like.
[0038] In addition, from the viewpoints of increasing the capacity of the battery and improving the power characteristics of the battery, the crystallite size s of the composite oxide (Z), which is calculated from the half-value width of the diffraction peak of the (104) plane in the X-ray diffraction spectrum based on X-ray diffraction using the Scherrer equation, is preferably in the range.
[0039] The X-ray diffraction spectrum is obtained using a powder X-ray diffractometer (manufactured by Rigaku Corporation, trade name "RINT-TTR", radiation source Cu-Kα) according to a powder X-ray diffraction method under the following conditions.
[0040] Measurement range: 15-120°
[0041] Scanning speed: 4° / minute
[0042] Resolution range: 30-120°
[0043] Background: B-spline
[0044] Curve functions: Segmentation-type fitting Voigt function
[0045] Bounding condition: Li(3a) + Ni(3a) = 1
[0046] Ni(3a) + Ni(3b) = α (α is the proportion of each Ni)
[0047] ICSD No.: 98-009-4814
[0048] The Scherrer formula is shown below. In the formula, s is the crystallite size, λ is the wavelength of the X-ray, B is the half-width of the diffraction peak of the (104) plane, θ is the diffraction angle (rad), and K is the Scherrer constant. In this embodiment, K is set to 0.9.
[0049] s=Kλ / Bcosθ
[0050] Furthermore, the BET specific surface area of the composite oxide (Z) is preferably 1 m². 2 / g~5m 2 The range is / g. The composite oxide (Z) is composed of the above-described components and thus has a BET specific surface area within this range, thereby improving the energy density of the cathode. The BET specific surface area can be measured, for example, using a commercially available measuring device such as the HM model-1201 from Macsorb Corporation.
[0051] Composite oxides (Z) can be synthesized, for example, by mixing and calcining a transition metal oxide containing Ni, Co, Mn, Al, etc., a Mo raw material, and a Li raw material such as lithium hydroxide (LiOH). Alternatively, when the composite oxide (Z) contains Zr, Ti, Nb, Ca, etc., Zr raw materials such as ZrO2, Ti raw materials such as TiO2, Nb raw materials such as Nb2O5·nH2O, and Ca raw materials such as Ca(OH)2 can be mixed with the aforementioned transition metal oxides, Mo raw materials, and Li raw materials and calcined. Composite oxides (Z) containing Ni and Mo can also be synthesized by mixing and calcining a transition metal oxide containing Ni, Co, Mn, Al, etc., a Mo raw material, and Zr, Ti, Nb, and Ca raw materials, followed by adding Li raw material and calcining again.
[0052] The firing process comprises a multi-stage firing procedure, which includes the following steps: a first firing step in a firing furnace, under an oxygen flow, at a first heating rate up to a first set temperature of 450°C or higher and 680°C or lower; and a second firing step in a firing furnace, under an oxygen flow, firing the product obtained in the first firing step at a second heating rate up to a second set temperature exceeding 680°C and below 800°C. Here, the first heating rate is in the range of 1.5°C / min or higher and 5.5°C / min or lower, and the second heating rate is slower than the first heating rate and in the range of 0.1°C / min or higher and 3.5°C / min or lower. Through this multi-stage firing process, the parameters of the lithium transition metal oxide obtained in this embodiment, such as the half-width of the diffraction peak of the (104) plane, the crystallite size of the aforementioned lithium transition metal composite oxide calculated according to the Scherer formula, the BET specific surface area, and the amount of Mo supplied to the negative electrode, can be adjusted to the range specified above.
[0053] The first set temperature in the first firing process, in order to adjust the parameters of the lithium transition metal oxide to the aforementioned specified range, is only required to be in the range of 450°C or higher and 680°C or lower, preferably in the range of 550°C or higher and 680°C or lower. Furthermore, the first heating rate in the first firing process, in order to adjust the parameters of the lithium transition metal oxide to the aforementioned specified range, is only required to be in the range of 1.5°C / min or higher and 5.5°C / min or lower, preferably in the range of 2.0°C / min or higher and 5.0°C / min or lower. It should be noted that the first heating rate only needs to be within the aforementioned range, and multiple rates can be set for each temperature range. The firing start temperature (initial temperature) of the first firing process is, for example, in the range of room temperature to 200°C or lower.
[0054] The holding time of the first set temperature in the first firing process is preferably 0 hours or more and 5 hours or less, more preferably 0 hours or more and 3 hours or less, in terms of adjusting the above-mentioned parameters of the lithium transition metal oxide to the range specified above. The holding time of the first set temperature refers to the time during which the first set temperature is maintained after it is reached.
[0055] The second set temperature in the second firing process, in order to adjust the above-mentioned parameters of the lithium transition metal oxide to the specified range, is only required to be in the range of 680°C or higher and 800°C or lower, preferably 680°C or higher and 750°C or lower. The second heating rate in the second firing process, in order to adjust the above-mentioned parameters of the lithium transition metal oxide to the specified range, is only required to be slower than the first heating rate and in the range of 0.1°C / min or higher and 3.5°C / min or lower, preferably 0.2°C / min or higher and 2.5°C / min or lower. It should be noted that the second heating rate only needs to be within the above-mentioned range, and multiple rates can be set for each temperature range. For example, if the first set temperature is lower than 680°C, the second heating rate can be divided into a heating rate A from the first set temperature to 680°C and a heating rate B from 680°C to the second set temperature. Heating rate B is preferably slower than heating rate A.
[0056] The holding time of the second set temperature in the second firing process is preferably 1 hour or more and 10 hours or less, more preferably 1 hour or more and 5 hours or less, in order to adjust the above-mentioned parameters of the lithium transition metal oxide to the range specified above. The holding time of the second set temperature refers to the time during which the second set temperature is maintained after it is reached.
[0057] In the oxygen flow of the multi-stage firing process, in terms of adjusting the above-mentioned parameters of the lithium transition metal oxide to the specified range, for example, it is preferable to set the oxygen concentration in the oxygen flow to 60% or more and the oxygen flow rate to 10 cm³ / s. 3 The firing rate in the furnace is in the range of 0.2 mL / min to 4 mL / min, and the flow rate is 0.3 L / min or more per 1 kg of mixture. Furthermore, the maximum pressure applied inside the firing furnace is preferably set to a range of 0.1 kPa or more and 1.0 kPa or less, excluding the pressure outside the firing furnace.
[0058] The composite oxide (Z) obtained in the above process is washed with water, mixed with W or B raw materials, and then heat-treated to make the composite oxide (Z) contain W or B. Alternatively, the composite oxide (Z) obtained in the above process can be mixed with W or B raw materials and then heat-treated to make the composite oxide (Z) contain W or B. The heat treatment is carried out, for example, in a vacuum, in an oxygen stream, or in the atmosphere, at a temperature of 150°C to 600°C. Examples of W raw materials include tungsten oxide (WO3), lithium tungstate (Li2WO4, Li4WO5, Li6W2O9), etc. Examples of B raw materials include boric acid (H3BO3), lithium borate (Li2B4O7, Li3BO3, LiB3O5, LiBO2), etc.
[0059] [negative electrode]
[0060] The negative electrode 12 has a negative electrode core and a negative electrode composite material layer disposed on the surface of the negative electrode core. The negative electrode core may use a foil of a metal stable within the potential range of the negative electrode 12, such as copper, or a thin film of the metal disposed on its surface. The negative electrode composite material layer comprises a negative electrode active material and a binder material, and is preferably disposed on both sides of the negative electrode core except for the portion connected to the negative electrode lead 21. The negative electrode 12 can be manufactured, for example, by coating the surface of the negative electrode core with a negative electrode composite material slurry comprising a negative electrode active material and a binder material, drying the coating, and then compressing it to form a negative electrode composite material layer on both sides of the negative electrode core.
[0061] The negative electrode composite material layer includes, for example, a carbon-based active material that reversibly absorbs and releases lithium ions as the negative electrode active material. Suitable carbon-based active materials include natural graphite such as flake graphite, block graphite, and amorphous graphite, as well as artificial graphite such as blocky graphite (MAG) and graphitized mesophase carbon microspheres (MCMB). Alternatively, the negative electrode active material can be a Si-based active material composed of at least one of Si and Si-containing compounds, or a combination of carbon-based and Si-based active materials can be used.
[0062] The binder material contained in the negative electrode composite layer can be, similarly to that in the case of the positive electrode 11, fluoropolymers, PAN, polyimide, acrylic resins, polyolefins, etc., but styrene-butadiene rubber (SBR) is preferred. Furthermore, the negative electrode composite layer preferably also contains CMC or its salts, polyacrylic acid (PAA) or its salts, polyvinyl alcohol (PVA), etc. Suitablely, SBR is used in combination with CMC or its salts, and PAA or its salts.
[0063] The negative electrode 12 has a Mo-containing coating (hereinafter sometimes referred to as "negative electrode coating") formed on the surface of the negative electrode composite layer. It is believed that the negative electrode coating is formed by the deposition of Mo from the composite oxide (Z) dissolved during charge and discharge onto the surface of the negative electrode composite layer. That is, the negative electrode coating contains Mo derived from the composite oxide (Z). The negative electrode coating is formed, for example, by charge and discharge cycles of less than 10 cycles. By using a composite oxide (Z) containing a specified amount of Mo, a high-quality coating containing Mo derived from the positive electrode is formed on the surface of the negative electrode, thereby suppressing capacity reduction during charge and discharge and obtaining good cycle characteristics. The presence of the negative electrode coating can be confirmed, for example, by X-ray photoelectron spectroscopy (XPS).
[0064] The Mo content in the negative electrode, relative to the total mass of the lithium transition metal complex oxide in the positive electrode, ranges from 0.5 ppm to 120 ppm. When the Mo content is below 0.5 ppm or above 120 ppm, no improvement in charge-discharge cycle characteristics is achieved. The Mo content in the negative electrode can be controlled based on the composition of the complex oxide (Z), particularly the sintering conditions of the lithium transition metal complex oxide, the Mo content, and the charge-discharge conditions. For example, increasing the charge termination voltage or deepening the discharge depth tends to increase the Mo content in the negative electrode.
[0065] The Mo content in the negative electrode composite layer and coating can be calculated using the following method. Similarly, the Ni content in the negative electrode, as described later, can also be calculated using the same method.
[0066] (1) Add ion-exchange water to the negative electrode 12 to de-embed the negative electrode composite material layer and the coating from the negative electrode core.
[0067] (2) Aqua regia and hydrofluoric acid were added to the deintercalated negative electrode composite material layer and the coating and heated to dissolve them. Insoluble components such as carbon were filtered out to prepare an aqueous solution. The aqueous solution was diluted with ion-exchanged water, and the Mo concentration was determined by ICP-AES. The result was taken as the Mo content in the negative electrode.
[0068] The content of Mo in the negative electrode determined in (3)(2) is divided by the weight of lithium transition metal complex oxide in the positive electrode to obtain the Mo content in the negative electrode.
[0069] The negative electrode coating may also contain Ni. It is believed that Ni from the composite oxide (Z) dissolved during charging and discharging is deposited together with Nb and M on the surface of the negative electrode composite material layer to form the negative electrode coating. That is, the negative electrode coating contains Ni derived from the composite oxide (Z).
[0070] In the negative electrode, the mass ratio of Mo to Ni (Mo / Ni) is preferably 0.5 to 20, more preferably 2 to 18. A Mo / Ni ratio of 0.5 to 20 can improve the cycling performance. Furthermore, a Mo / Ni ratio of 2 to 18 can further improve the cycling performance. The Mo / Ni ratio can be controlled based on the composition of the composite oxide (Z), the sintering conditions of the lithium transition metal composite oxide, and the charge / discharge conditions.
[0071] The negative electrode coating may contain metallic elements other than Mo and Ni. For example, if the composite oxide (Z) contains at least one of Al or Mn, the negative electrode coating may also contain at least one of Al or Mn. Additionally, if the composite oxide (Z) contains W, the negative electrode coating may also contain W. Besides metallic elements such as Mo and Ni, the negative electrode coating may also contain organic matter as a decomposition product of the electrolyte.
[0072] [Separator]
[0073] The separator 13 uses a porous sheet with ion permeability and insulation. Specific examples of porous sheets include microporous films, woven fabrics, and nonwoven fabrics. Suitable materials for the separator 13 include polyolefins such as polyethylene and polypropylene, and cellulose. The separator 13 can be a single-layer structure or a multilayer structure. A heat-resistant layer can be formed on the surface of the separator.
[0074] Example
[0075] The present disclosure will be further described below with reference to embodiments, but the present disclosure is not limited to these embodiments.
[0076] <Example 1>
[0077] Synthesis of Lithium Transition Metal Composite Oxides (Positive Electrode Active Materials)
[0078] general formula Ni 0.85 Mn 0.15 The composite oxide shown in O2 was mixed with Li2MoO4 and lithium hydroxide monohydrate (LiOH·H2O) at a molar ratio of Ni, Mn, and Mo to Li of 1:1.08. This mixture was then fed into a calcining furnace and subjected to an oxygen flow of 95% oxygen concentration (per 10 cm³). 3 The mixture was calcined from room temperature to 650°C at a flow rate of 2 mL / min and 5 L / min per 1 kg of mixture, with a heating rate of 2.0°C / min. Then, it was calcined from 650°C to 780°C at a heating rate of 1°C / min. The calcined product was washed with water to obtain a lithium transition metal composite oxide. The composition of the lithium transition metal composite oxide was analyzed by ICP-AES, and the results showed that Li... 0.97 Ni 0.84 Mo 0.01 Mn 0.15 O2.
[0079] [The production of the positive electrode]
[0080] The aforementioned lithium transition metal composite oxide was used as the positive electrode active material. The positive electrode active material was mixed with acetylene black and polyvinylidene fluoride (PVdF) at a solid component mass ratio of 95:3:2. An appropriate amount of N-methyl-2-pyrrolidone (NMP) was added, and the mixture was then kneaded to prepare a positive electrode composite slurry. This positive electrode composite slurry was coated onto both sides of a positive electrode core formed from aluminum foil. After the coating dried, it was calendered using rollers and cut into specified electrode sizes, resulting in a positive electrode with a positive electrode composite layer formed on both sides of the positive electrode core. It should be noted that a portion of the positive electrode has an exposed portion where the surface of the positive electrode core is exposed.
[0081] [Making the negative electrode]
[0082] Natural graphite was used as the negative electrode active material. The negative electrode active material was mixed with sodium carboxymethyl cellulose (CMC-Na) and styrene-butadiene rubber (SBR) in an aqueous solution at a solid component mass ratio of 100:1:1 to prepare a negative electrode composite slurry. This negative electrode composite slurry was coated onto both sides of a negative electrode core formed from copper foil. After the coating dried, it was calendered using rollers and cut into specified electrode sizes to obtain a negative electrode with a negative electrode composite layer formed on both sides of the negative electrode core. It should be noted that a portion of the negative electrode has an exposed portion where the surface of the negative electrode core is exposed.
[0083] [Preparation of non-aqueous electrolytes]
[0084] A non-aqueous electrolyte was prepared by dissolving lithium hexafluoride phosphate (LiPF6) at a concentration of 1.2 mol / L in a mixed solvent containing ethylene carbonate (EC), ethyl methyl carbonate (MEC), and dimethyl carbonate (DMC) in a volume ratio of 3:3:4.
[0085] [Preparation of the experimental battery cell (non-aqueous electrolyte secondary battery)]
[0086] An aluminum lead is installed on the exposed portion of the positive electrode, and a nickel lead is installed on the exposed portion of the negative electrode. The positive and negative electrodes are wound in a spiral shape with a polyolefin separator in between, and then pressed radially to form a flat, wound electrode body. This electrode body is housed in a housing made of aluminum laminate, and the non-aqueous electrolyte is injected. The opening of the housing is then sealed to obtain the test battery cell.
[0087] [Evaluation of capacity retention after cyclic testing]
[0088] For the test battery cells described above, a constant current charging process was performed at 25°C with a constant current of 0.5 It until the battery voltage reached 4.2V. Then, a constant voltage charging process was performed at 4.2V until the current reached 1 / 50 It. Afterward, a constant current discharge process was performed with a constant current of 0.5 It until the battery voltage reached 2.85V. This charge-discharge cycle was repeated 100 times. The discharge capacity of the first cycle and the discharge capacity of the 100th cycle were determined, and the capacity retention rate was calculated using the following formula.
[0089] Capacity retention (%) = (Discharge capacity in the 100th cycle ÷ Discharge capacity in the 1st cycle) × 100
[0090] <Example 2>
[0091] In the synthesis of the positive electrode active material, Ni, Mn, and Mo are synthesized in a molar ratio of 1:1.01 to Li. 0.85 Mn 0.15 O2, Li2MoO4, and LiOH·H2O were mixed and calcined at 750°C. Otherwise, test battery cells were fabricated and their performance was evaluated in the same manner as in Example 1.
[0092] <Example 3>
[0093] In the synthesis of the positive electrode active material, Ni, Mn, and Mo are synthesized in a molar ratio of 1:1.05 to Li. 0.85 Mn 0.15 O2, Li2MoO4, and LiOH·H2O were mixed, and experimental battery cells were fabricated and their performance evaluated in the same manner as in Example 1.
[0094] <Example 4>
[0095] In the synthesis of positive electrode active materials, the general formula Ni is used. 0.91 Co 0.04 Al 0.05 The composite oxide shown in O2 was mixed with Li2MoO4 and LiOH·H2O in a molar ratio of Ni, Co, Al and Mo to Li of 1:1.05, and the firing temperature was 720°C. Otherwise, the test battery cells were fabricated and their performance was evaluated in the same manner as in Example 1.
[0096] <Example 5>
[0097] In the synthesis of positive electrode active materials, the general formula Ni is used. 0.94 Co 0.06The composite oxide shown in O2 was mixed with Li2MoO4, Ti(OH)4 and LiOH·H2O in a molar ratio of Ni, Co, Mo and Ti to Li of 1:1.05, and the firing temperature was 720°C. Otherwise, the test battery cells were fabricated and their performance was evaluated in the same manner as in Example 1.
[0098] <Example 6>
[0099] In the synthesis of positive electrode active materials, the general formula Ni is used. 0.955 Al 0.045 The composite oxide shown in O2 was mixed with Li2MoO4, Nb2O5, and LiOH·H2O at a molar ratio of Ni, Co, Mo, and Nb to Li of 1:1.03. The mixture was then calcined from room temperature to 600°C at a heating rate of 2.0°C / min. Subsequently, it was calcined from 600°C to 700°C at a heating rate of 0.5°C / min. Otherwise, test battery cells were fabricated and their performance evaluated in the same manner as in Example 1.
[0100] <Example 7>
[0101] In the synthesis of positive electrode active materials, the general formula Ni is used. 0.955 Al 0.045 The composite oxide shown in O2 was mixed with Li2MoO4, Ca(OH)2, and LiOH·H2O in a molar ratio of Ni, Co, Mo, and Ca to Li of 1:1.03. The mixture was then calcined from room temperature to 600°C at a heating rate of 2.0°C / min. Subsequently, it was calcined from 600°C to 700°C at a heating rate of 0.5°C / min and used. Otherwise, test battery cells were fabricated and their performance evaluated in the same manner as in Example 1.
[0102] <Comparative Example 1>
[0103] In the synthesis of positive electrode active materials, the general formula Ni is used. 0.85 Mn 0.15 The composite oxide shown in O2 was mixed with Li2MoO4 and LiOH·H2O at a molar ratio of Ni, Mn, and Mo to Li of 1:1.12, and calcined from room temperature to 600°C at a heating rate of 6.0°C / min. Then, it was calcined from 600°C to 730°C at a heating rate of 3°C / min. Otherwise, the test battery cells were fabricated in the same manner as in Example 1.
[0104] <Comparative Example 2>
[0105] In the synthesis of positive electrode active materials, the general formula Ni is used. 0.85 Mn 0.15The composite oxide shown in O2 was mixed with LiOH·H2O in a molar ratio of the total amount of Ni and Mn to Li of 1:1.08. Otherwise, test battery cells were fabricated and their performance was evaluated in the same manner as in Example 1.
[0106] <Comparative Example 3>
[0107] In the synthesis of positive electrode active materials, the general formula Ni is used. 0.91 Co 0.04 Al 0.05 The composite oxide shown in O2 was mixed with Li2MoO4 and LiOH·H2O in a molar ratio of Ni, Co, Al and Mo to Li of 1:1.05, and the firing temperature was 730°C. Otherwise, the test battery cells were fabricated and their performance was evaluated in the same manner as in Example 1.
[0108] <Comparative Example 4>
[0109] In the synthesis of positive electrode active materials, the general formula Ni is used. 0.89 Co 0.06 Al 0.05 The composite oxide shown in O2 was mixed with Li2MoO4 and LiOH·H2O at a molar ratio of Ni, Co, Al, and Mo to Li of 1:1.05. The mixture was then calcined from room temperature to 600°C at a heating rate of 2.0°C / min. Subsequently, it was calcined from 600°C to 800°C at a heating rate of 3°C / min and used. Otherwise, test battery cells were fabricated and their performance was evaluated in the same manner as in Example 1.
[0110] <Comparative Example 5>
[0111] In the synthesis of positive electrode active materials, the general formula Ni is used. 0.94 Co 0.01 Al 0.05 The composite oxide shown in O2 was mixed with LiOH·H2O in a molar ratio of Ni, Co and Al to Li of 1:1.02. Otherwise, the test cell was made in the same manner as in Example 1.
[0112] The capacity retention rates of the examples and comparative examples are shown in Table 1. Table 1 also shows the composition and characteristics of the positive electrode active material, as well as the Mo content and Mo / Ni ratio in the negative electrode. It should be noted that the Mo content and Mo / Ni ratio in the negative electrode were determined by measuring the negative electrode taken from the test battery cell after cycle testing. In addition, XPS confirmed that in any of the negative electrodes of Examples 1 to 7, a negative electrode coating was formed on the surface of the negative electrode composite layer.
[0113] [Table 1]
[0114]
[0115] As shown in Table 1, the test battery cells of the embodiments exhibited higher capacity retention and superior charge-discharge cycle characteristics after cycle testing compared to the test battery cells of the comparative examples. In the test battery cells of the embodiments, a positive electrode active material containing Mo at a ratio of less than 3 mol% was used, and a coating containing Mo derived from the positive electrode active material at a ratio of 0.5 ppm to 120 ppm was formed on the negative electrode surface. On the other hand, the test battery cells of Comparative Examples 2 and 5 did not contain Mo in the positive electrode active material, and no Mo-containing coating was found on the negative electrode surface. The test battery cell of Comparative Example 4 contained Mo in the positive electrode active material, but a sufficient Mo-containing coating was not formed on the negative electrode surface. Furthermore, the Mo content in the positive electrode active material of the test battery cell of Comparative Example 3 was too high, which was considered to hinder the formation of the layered structure of the positive electrode active material, resulting in structural instability. Additionally, the Mo content in the negative electrode of the test battery cell of Comparative Example 1 was too high, which was considered to lead to excessive coating formation and increased resistance. Therefore, by using a positive electrode active material containing a specified amount of Mo and a negative electrode coating containing a specified amount of Mo derived from the positive electrode active material, the charge-discharge cycle characteristics of the battery are significantly improved.
[0116] Explanation of reference numerals in the attached figures
[0117] 10 Secondary battery, 11 Positive electrode, 12 Negative electrode, 13 Separator, 14 Electrode body, 16 Outer casing, 17 Sealing body, 18, 19 Insulating board, 20 Positive lead, 21 Negative lead, 22 Groove section, 23 Internal terminal board, 24 Lower valve body, 25 Insulating component, 26 Upper valve body, 27 Cover, 28 Gasket
Claims
1. A non-aqueous electrolyte secondary battery, comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte. The positive electrode comprises a lithium transition metal composite oxide, which has a layered structure and contains at least Ni and Mo. In the lithium transition metal composite oxide The Ni content is 80 mol% to 95 mol% relative to the total moles of metals other than Li. The content of Mo is less than 3 mol% relative to the total moles of metal elements other than Li. The negative electrode comprises: a negative electrode composite material layer containing a negative electrode active material, and a Mo-containing coating formed on the surface of the negative electrode composite material layer. The content of Mo in the negative electrode is 0.5 ppm to 120 ppm relative to the total mass of the lithium transition metal composite oxide in the positive electrode.
2. The non-aqueous electrolyte secondary battery according to claim 1, wherein, The coating also contains Ni.
3. The non-aqueous electrolyte secondary battery according to claim 2, wherein, The mass ratio of Mo to Ni in the negative electrode, i.e., Mo / Ni, is 0.5~20.
4. The non-aqueous electrolyte secondary battery according to claim 2, wherein, The mass ratio of Mo to Ni in the negative electrode, i.e., Mo / Ni, is 2~18.
5. The non-aqueous electrolyte secondary battery according to any one of claims 1 to 4, wherein, The lithium transition metal composite oxide further contains at least one of Al or Mn. The coating also contains at least one of Al or Mn.
6. The non-aqueous electrolyte secondary battery according to any one of claims 1 to 4, wherein, The half-width of the diffraction peaks on the (104) plane of the X-ray diffraction pattern based on X-ray diffraction, and the crystallite size of the lithium transition metal composite oxide calculated according to the Scherer formula, are in the range of 250 Å to 800 Å.
7. The non-aqueous electrolyte secondary battery according to any one of claims 1 to 4, wherein, The BET specific surface area of the lithium transition metal composite oxide is 1 m². 2 / g~5m 2 The range of / g.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery
JP2006310181A
Lithium transition metal system compound powder, method of manufacturing the same, and spray-dried material to become its calcination precursor, and positive electrode for lithium secondary battery using the same, and lithium secondary cell
JP2009289726A
Composite cathode active material, cathode and lithium battery including the composite cathode active material, and method of preparing the composite cathode active material
US20180316009A1